Simulating the Impact of Daytime Calibration in the Behavior of a Closed Loop Proportional Lighting Control System - Aris Tsangrassoulis (MDPI AG, 2021)
A daylighting control system that uses the closed loop proportional algorithm needs to be calibrated both during nighttime and daytime. The selection of the daytime calibration time can affect the behavior of the system and is usually performed when the ratio of the illuminance of the ceiling sensor (SD,tc) to the illuminance at a point on the working plane (ED,tc) is relatively large without sunlight patches in the ceiling photo-sensor’s field of view (FOV). However, this requirement is not associated with a specific value and can be achieved under a wide range of conditions related to the sky luminance distribution. In the present work, four ceiling sensors with different field of views (FOVs) were examined in a typical north-facing office space. The effect of daytime calibration on the system’s performance was estimated through the calculation of lighting energy savings and the overdimming percentage. The results show that the effect of both the FOV of the ceiling sensor and the daytime calibration period is small except for the case of the sensor without cover, especially when it is close to the opening. In an attempt to quantify the SDtc/IDtc ratio, a new magnitude (RR) is proposed by dividing the illuminance ratios of the ceiling photo-sensor by that on the working surface during daytime and nighttime calibration. Thus, the daily calibration of the sensors with cover can be performed when RR > 1.